Persepsi abang none Jakarta terhadap fenomena ondel-ondel ngamen di Jakarta - Ardiansyah, Lutfi (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2021)
Ondel-Ondel is one of Betawi special icon an also one of the artworks of Betawi. This giant puppet also believed as a charm in Betawi society for decades. People of Betawi also considered Ondel-Ondel as a sacred culture. Ondel-Ondel is an entertainment for Betawi society that inherited from generation to generation. However, nowadays ondel-ondel is not considered as a sacred property for ritual any longer since the last couple of years. Ondel-ondel has been used for busking in every corner of Jakarta. The aim of this research was to find out the perception of Abang None as the ambassador of tourism to conserve the culture of Betawi regarding the phenomenon Ondel-Ondel that busking on the street. We collected the data by using observation, profound interview, literature review and online data research. This research used the concept of communication and culture theory and it is also a qualitative and descriptive research by using phenomenology and case study method. The result of this research is the Abang None about the difference between the properties of busking ondel-ondel and the Betawiâ€™s entertainment ondel-ondel. Abang None is the disagreement with the busking ondel-ondel since it looked so pity and inappropriate, and Abang None is they would not give the money to the busking ondel-ondel.Â Keywords:Â Abang None; Ondel-Ondel; Betawi Culture; Perception.